United Nations Peacekeeping Operations and the Use of Fforce - Ruth Wedgwood (Washington University Journal of Law & Policy, 2001)
When one views the UN up close, in the field and in New York, much of the unsteadiness in discharging its missions stems from the organization’s deep ambivalence about the proper use of force in international conflict resolution and its hobbled ability to muster efficacious force.
Keywords: Human rights; United Nations; Peacekeeping forces